SDF‐1/CXCR4 signalling is involved in blood vessel growth and remodelling by intussusception. Issue 6 (4th April 2019) - Dimova, Ivanka; Karthik, Swapna; Makanya, Andrew; Hlushchuk, Ruslan; Semela, David; Volarevic, Vladislav; Djonov, Valentin
Abstract: The precise mechanisms of SDF‐1 (CXCL12) in angiogenesis are not fully elucidated. Recently, we showed that Notch inhibition induces extensive intussusceptive angiogenesis by recruitment of mononuclear cells and it was associated with increased levels of SDF‐1 and CXCR4. In the current study, we demonstrated SDF‐1 expression in liver sinusoidal vessels of Notch1 knockout mice with regenerative hyperplasia by means of intussusception, but we did not detect any SDF‐1 expression in wild‐type mice with normal liver vessel structure. In addition, pharmacological inhibition of SDF‐1/CXCR4 signalling by AMD3100 perturbs intussusceptive vascular growth and abolishes mononuclear cell recruitment in the chicken area vasculosa. In contrast, treatment with recombinant SDF‐1 protein increased microvascular density by 34% through augmentation of pillar number compared to controls. The number of extravasating mononuclear cells was four times higher after SDF‐1 application and two times less after blocking this pathway. Bone marrow‐derived mononuclear cells (BMDC) were recruited to vessels in response to elevated expression of SDF‐1 in endothelial cells. They participated in formation and stabilization of pillars. The current study is the first report to implicate SDF‐1/CXCR4 signalling in intussusceptive angiogenesis and further highlights the stabilizing role of BMDC in the formation of pillars during vascular remodelling.